2022
DOI: 10.37231/ajmb.2022.6.2.468
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Approaches for Pain Management in Post-Operative Total Knee Replacement

Abstract: Pain management is very crucial in nursing care. However due to lack of overall understanding, pain management by health professional is scarce. Therefore, knowledge and attitude of nurses towards effective management of pain in care post-operative care is pertinent. The effectiveness of postoperative nursing care is a basic part of a healthcare worker. The type of post-operative management emphasized in this article consists of the pain assessment and pain management by pharmacological and non-pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A comparison of previous studies that reported preoperative and postoperative outcome scores for patients of TKR showed that the procedure was effective [25]. The mentioned studies included patients of various ages and used a variety of prostheses and techniques to implant the device [26, 27]. TKR was effective in all of the studies [26, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of previous studies that reported preoperative and postoperative outcome scores for patients of TKR showed that the procedure was effective [25]. The mentioned studies included patients of various ages and used a variety of prostheses and techniques to implant the device [26, 27]. TKR was effective in all of the studies [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned studies included patients of various ages and used a variety of prostheses and techniques to implant the device [26,27]. TKR was effective in all of the studies [26,27]. Furthermore, unicompartmental knee replacement (UKR) surgery seems to be as effective as TKR surgery for people who have the indications for it.…”
Section: Figurementioning
confidence: 99%
“…is prevalent, affecting approximately 50% of patients following procedures like thoracotomy and mastectomy [4][5][6].…”
Section: Introductionmentioning
confidence: 99%